Pelatihan Pemanfaatan Editing Vidio Sebagai Media Dalam Pembelajaran Serta Pemasaran Berbasis Ict Dimasa Pandemi Covid-19 - Imam Mutaqin; Abu Zaini (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
In the excitement of community service this time which was carried out in the hamlet of Sumbersari-Kencong-Kepung Kediri. Which was held for a period of 3 weeks starting from July 26, 2021 until August 26, 2021. Various KKN-DR activities start from observation, program planning, program consultation in accordance with the planned program, namely the KKN-DR activity held in the form of vidio edting training with the title "training on the use of vidio edting as a medium in ICT-based learning and marketing during the COVID-19 pandemic". The work of this report is shown to provide vidio editing training for educational needs and personal interests and provide an understanding of the importance of interesting learning media during the Covid-19 pandemic. The result of this ilmiyah work is the sumbersari community who participate in vidio edting training in increasing the needs needed and to utilize this increasingly sophisticated HP media.